Особенности распространения и экологии листоедов рода лупер — Luperus Geoffr. (Coleoptera, Chrysomelidae) на Украине - Бровдий, В.М. (Вестник зоологии, 1972)
Eleven species of leaf beetles of the genus Luperus G e o f f r. are registered in the Ukrainian fauna. They inhabit low lands and highlands. Imago of most species feed on leaves of different fruit trees and forest cultures. L. xanthopoda S c h r a n k. L. flavipes L., L. longicornis F. feeding on apple-, pear-, plum-, apricot-, cherry-trees, oak, elm, black thorn, hazel are the most harmful. The data are presented on distribution of different species found in the Ukrainian landscape zones, on their trophic relations, seasonal dynamics and on harmfulness of each of them separately.